E-government and State Governance in the Morden Time - Quan, Nguyen Van; Giao, Vu Cong (VNU Journal of Science: Legal Studies, 2019)
Currently, e-government is one of the important tools to improve the efficiency of state management and the quality of public services. E-government applications contribute to meeting the requirements of modern governance, such as publicity, transparency, accountability, timeliness of public administration and citizen participation. Therefore, e-government is being developed and applied by various countries in the world including Vietnam.